Matter that remembers, protects, works, feels, and mediates. Some remarks on the third edition of “The Lost and Found” symposium (Riga 2024) - Agnieszka Patała (Quart)
The text provides a brief summary of “The Lost and Found: Revising Art Stories in Search of Potential Changes” symposium’s third edition, held in Riga on 6–7 June 2024, organised in collaboration with Latvijas Mākslas Akadēmija, the University of Wrocław, and Universidade Nova de Lisboa. During two intense days of discussions, talks, and workshops, artists and art theorists investigated how matter shapes and influences inclusive and holistic relationships between humans and non-humans. They examined matter’s sensory and emotional capacities alongside its function in fostering a safe space where vulnerability and weakness can be freely explored. The analysis also focused on how matter contributes to creating, maintaining, and utilizing safe, inviting, and communal shelters where all beings needing care can find their refugium. Textiles held a unique significance here, especially regarding the collaborative and bonding processes inherent in their creation, including techniques like weaving and knitting.